Sistem Kendali dan Strategi Penanganan (Manajemen) Krisis Dalam Kajian Public Relations - Arief Fajar (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2011)
The role of Public Relations, especially in aspects of management (Public Relations Management) to handle issues and crises will greatly depend on the type and systems as an organization. According to Anne Gregory at least in Crisis Management, PR is able to communicate to management about the structure of stakeholder from organizations and their characteristics which are expected to support the policy.